“Like a Double-edged Sword”: Student Testimonials on Campus Carry in Texas - Malla Lehtonen; Mila Seppälä (Cambridge University Press, 2022)
Undergraduates from three Texas universities were given free rein to draw and write about their experiences with the state's Campus Carry law. Through analyzing the personal stories, rationalizations, poems, and drawings the students produced, we offer insight into how they view the law and how it has impacted their sense of security. What emerges is a complex picture, revealing that students hold inconsistent – or even contradictory – beliefs in the dichotomy of being either for or against guns on campus. This essay complements existing research on the Campus Carry debate by uncovering the ambivalence that quantitative approaches alone may not capture.